Multicultural Islamic Education in Crisis: Formalism, School Violence, and Leadership Failure - Hilmy Alwy Abdillah (Cakrawala Journal is a scientific journal published by Nahdlatul Ulama Islamic Institute (IAINU) Kebumen. This journal focuses on the Islamic Education Management Study and Social Studies which is published twice a year.IAINU Kebumen, 2026)
Multicultural Islamic education is widely promoted as a framework for fostering tolerance, moral integrity, and social harmony in Islamic schools. However, the increasing occurrence of bullying, school violence, and ethical misconduct within Islamic educational institutions raises critical questions about its practical effectiveness. This study aims to critically examine the crisis of multicultural Islamic education by analyzing its formalistic implementation, leadership failure, and weak policy commitment. Employing a qualitative approach with a library research design, this study analyzes scholarly literature on multicultural Islamic education, educational leadership, school management, and social dynamics in Islamic schools. The findings indicate that multicultural Islamic education is often implemented symbolically through curriculum and institutional rhetoric without being internalized as an ethical governance system. Leadership failure and the absence of enforceable value-based policies contribute to the normalization of violence and unequal power relations within schools. The study concludes that multicultural Islamic education remains relevant only when reconstructed as ethical governance that integrates value-based leadership, policy operationalization, professional ethical development, and inclusive school culture. Such reconstruction enables Islamic schools to move beyond formalism and restore their moral and educational authority.